Expectations for nursing care in newborn units in Kenya: moving from implicit to explicit standards. Issue 2 (21st March 2018) - Murphy, Georgina A V; Omondi, Gregory B; Gathara, David; Abuya, Nancy; Mwachiro, Jacintah; Kuria, Rose; Tallam-Kimaiyo, Edna; English, Mike
Abstract : Neonatal mortality currently accounts for 45% of all child mortality in Kenya, standing at 22 per 1000 live births. Access to basic but high quality inpatient neonatal services for small and sick newborns will be key in reducing neonatal mortality. Neonatal inpatient care is reliant on nursing care, yet explicit nursing standards for such care do not currently exist in Kenya. We reviewed the Nursing Council of Kenya 'Manual of Clinical Procedures' to identify tasks relevant for the care of inpatient neonates. An expert advisory group comprising major stakeholders, policy-makers, trainers, and frontline health-workers was invited to a workshop with the purpose of defining tasks for which nurses are responsible and the minimum standard with which these tasks should be delivered to inpatient neonates in Kenyan hospitals. Despite differences in opinions at the beginning of the process, consensus was reached on the minimum standards of neonatal nursing. The key outcome was a comprehensive list and grouping of neonatal nursing task and the minimum frequency with which these tasks should be performed. Second, a simple categorisation of neonatal patients based on care needs was agreed. In addition, acceptable forms of task sharing with other cadres and the patient's family for the neonatal nursing tasks were agreed and described. The process was found to be acceptable to policy-makers and practitioners, who recognised the value of standards in neonatal nursing to improve the quality of neonatal inpatient care. Such standards could form the basis for audit and quality evaluation.